Vendor Manager to Performance Enabler. Issue 4 (18th April 2016) - Araujo, Vincent
Abstract : The author was asked to identify the training needed to support a title change from Vendor Managers to Performance Enablers. But as a CPT expert, he dug deeper into why the change was being made and knew that the whole system needed to be evaluated. The author and his team worked with executives to not only identify key metrics, but to define what good looks like for the new role and the behaviors required to deliver successful outcomes. By conducting interviews and reviewing executive communications, the team was able to identify enablers and barriers to desired outputs. The key to success was not just the analysis; it was engaging key stakeholders in identifying problems and paths to improving performance. By focusing on the four principles of HPT—results, systems, value, and partnership (or RSVP)—the team expanded the scope of the request and delivered improved business value.